'Cool' Meanings: Tattoo Artists, Body Work and Organizational 'Bodyscape'. (February 2018) - Simpson, Ruth; Pullen, Alison
This article analyses the meanings tattooists as 'body workers' construct around their work. Based on an ethnographic study, the research finds that tattooists adhere to notions of non-conformity, unconventional artistry and professionalism. We locate these meanings within the cultural values and aesthetics of 'cool' as an admired set of attributes and displays which enable tattooists to manage some of the tensions of the work. Combining Bourdieu's concept of habitus with Gagliardi's notion of landscape, we develop the idea of 'bodyscape' to further an integrated understanding of body work as spatialized and embodied i.e. one which incorporates the significance of spatial practices and artefacts, the bodies of those worked upon and the embodied dispositions of workers.